Pete the cat and the missing cupcakes - Dean, Kim 1969-; Dean, James 1957- (Harper, an imprint of HarperCollinsPublishers, 2016)
Pete and his friends must solve a mystery when some of the cupcakes they have backed for a party go missing!
Keywords: Pete / the Cat (Fictitious character) / Juvenile fiction; Pete / the Cat (Fictitious character) / Fiction; Pete / the Cat (Fictitious character); Cats / Juvenile fiction; Cupcakes / Juvenile fiction; Friendship / Juvenile fiction; Cats / Fiction; Cupcakes / Fiction; Friendship / Fiction; Animals / Fiction; JUVENILE FICTION / Cooking & Food; JUVENILE FICTION / Social Themes / Emotions & Feelings; JUVENILE FICTION / Social Themes / Manners & Etiquette; Cats; Cupcakes; Friendship; Kater; Verschwinden; Freundschaft; Muffin; Tiere; Aufklärung -- Kriminologie; Party; Bilderbuch